Методи та засоби автоматизованого контролю зубчастого профілю роторів планетарних гідромашин - Панченко, Анатолій Іванович; Волошина, Анжела Анатоліївна; Ковязін, Олексій Сергійович; Панченко, Ігор Анатолійович; Волошин, Анатолій Анатолійович; Panchenko, Anatolii; Voloshina, Angela; Koviazin, Oleksii; Panchenko, Ihor; Voloshin, Anatolii (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У гідроприводах сучасної самохідної техніки все більше застосування знаходять гідравлічні машини планетарного типу. Одним з основних вузлів цих гідромашин є система роторів із зубчастими поверхнями. Точність виготовлення геометрії зубчастого профілю роторів визначає працездатність планетарної гідромашини. В результаті проведених досліджень обґрунтовано методологічну можливість автоматизації контролю зубчастої поверхні роторів планетарних гідромашин. З метою визначення контрольованих параметрів розроблено розрахункову схему системи роторів планетарної гідромашини та отримано математичні залежності, що описують елементи конструкції вимірювальних пристроїв. Виробнича перевірка розроблених засобів автоматизованого контролю роторів показала, що запропонований метод контролю дозволяє здійснити прецизійне складання системи роторів планетарних гідромашин шляхом селективного підбору відповідних пар. /// EN: Planetary hydraulic machines are increasingly used in hydraulic drives for construction, railway, drilling, and other self-propelled equipment. One of the key components of these hydraulic machines is the rotor system, which is a precision pair of rotors with toothed surfaces. Thus, the rotor system is a moving precision pair with a complex toothed surface, and the manufacturing accuracy of the rotor tooth profile geometry determines the performance of the planetary hydraulic machine as a whole. Ensuring the necessary sealing in the planetary hydraulic machine rotor system for distributing high and low pressure zones is achieved through selective rotor selection. This requires the development of appropriate methods and tools for automated monitoring of deviations in measured parameters determined by the toothed surfaces of the inner and outer rotors. Therefore, issues related to the development of methods and tools for automated testing of the toothed profile of planetary hydraulic machine rotors to ensure precision assembly of the rotor system are a relevant area of research. This paper substantiates the methodological feasibility of automating the testing of the toothed surface of planetary hydraulic machine rotors. To determine the controlled parameters, a design scheme for the rotor system of a planetary hydraulic machine was developed, and mathematical relationships were derived describing the design elements of the measuring devices. A gear pair with internal hypocycloidal engagement was selected for production testing of the developed testing tools. The kinematic and geometric parameters of the inner and outer rotors are, respectively, equal to: number of teeth – z1 = 11 and z2 = 12; tooth curvature radii – r1 = r2 = 7.0 mm; tooth center radii – R1 = 33.35 mm and R2 = 45.0 mm; eccentricity – e = 2.35 mm. A production test of the developed automated rotor testing tools demonstrated that the proposed testing method enables the precise assembly of planetary hydraulic machine rotor systems through the selective selection of appropriate pairs.
Methods and Means of Automated Control of the Toothed Profile of Rotors of Planetary Hydraulic Machines
Keywords: система роторів; зубчастий профіль; автоматизований контроль; вимірювальні пристрої; селективний підбір; rotor system; toothed profile; automated control; measuring devices; selective selection